Perspektif Filosofis Peran Pancasila dalam Tata Pemerintahan Indonesia Kontemporer - Wijayanto, Wiwit Sigit; Suharto, Toto; Martadinata, Edly Restu Caesar; Putra, Wira Dwi; Hidayat (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Pancasila, as the philosophical foundation of the state, serves as the normative foundation for governance in Indonesia. However, studies on Pancasila in governance are still dominated by normative discussions, while analyses linking Pancasila values ​​to good governance practices and the challenges of bureaucratic reform are still limited. This study aims to analyze the position and function of Pancasila as a grundnorm in building good governance and identify gaps between philosophical values ​​and their implementation in contemporary governance. The study uses a library research approach with descriptive-analytical methods and philosophical hermeneutics. The primary data sources are literature on Pancasila philosophy, laws and regulations, governance policy documents, and scientific articles discussing Pancasila and good governance. The analysis shows that Pancasila forms three main dimensions of governance: legitimacy of power, deliberation-based decision-making, and social justice orientation in public policy. The analysis also reveals a gap between the philosophical values ​​of Pancasila and governance practices, which are still oriented towards procedural compliance without substantive internalization of these values. This research offers a reconstruction of Pancasila as a public ethical framework through a conceptual model that integrates regulatory aspects, institutional capacity strengthening, and evaluation of social justice-based governance.